Core Ethical Values of Character Education Based on National Cultural Values in Madrasah - Muhammad Syauqi Mubarok; Aan Hasanah; Bambang Samsul Arifin (Edumaspul: Jurnal Pendidikan, 2023)
Character education is important in shaping the character of quality students. The implementation of character education based on national cultural values in madrasah is very important to foster students' moral and ethical awareness. This research aims to find out the importance of character education based on national cultural values in madrasas, the phenomenon of problems that arise, and solutions to overcome these problems. The research method used is descriptive method with data collection techniques through observation, interviews, and documentation studies. Respondents in this study were principals, teachers, and students in one of the madrasahs in Indonesia. The results showed that character education based on national cultural values in madrasah is very important in shaping the character of quality students. The implementation of national culture-based character education can be done through subjects and extracurricular activities as well as building a conducive school environment. However, there are several challenges that must be faced, such as students' lack of understanding of the importance of character education, lack of support from the principal and teachers, and lack of adequate resources. In conclusion, the implementation of character education based on national cultural values in madrasah is very important in shaping the character of qualified students who have high moral awareness. Therefore, there needs to be continuous support and efforts from the principal, teachers, and all stakeholders in strengthening the implementation of national culture-based character education in madrasah.